Extended Kalman filter and adaptive backstepping for mean temperature control of a three‐way catalytic converter. (2nd September 2013) - Utz, T.; Fleck, C.; Frauhammer, J.; Seiler‐Thull, D.; Kugi, A.
SUMMARY This contribution is concerned with an adaptive control strategy for the mean temperature of an automotive three‐way catalytic converter. Tailored finite‐dimensional approximations of the complex infinite‐dimensional mathematical model of the catalytic converter serve as a basis for the design of an extended Kalman filter for state profile estimation and of an adaptive backstepping controller for the mean temperature. Although the model used for observer design relies on (semi‐)discretising the infinite‐dimensional model, a simple model for the mean temperature employing a phenomenological approach to describe the reaction heat is used for control design. The observer/controller is tested in simulation scenarios using a validated model of the three‐way catalytic converter. Copyright © 2013 John Wiley & Sons, Ltd.